Macroscopic Fungi Diversity Around Community Forest Areas in Suka Makmur Village, Kutalimbaru District Deli Serdang Regency North Sumatra - Sihombing, Saroh Maduma; Jayanthi, Sri; Pandia, Ekariana S (Jurnal Biologi Tropis, 2024)
Fungi are one of various types of organisms that play an important role in maintaining balance and preserving nature. Fungi act as decomposers of organic material in forest ecosystems, thus helping to fertilize the soil by providing nutrients for plants. This research aims to determine the types of macroscopic fungi around the Community Forest area, determine the diversity index of macroscopic fungal species and determine the characteristics of the macroscopic fungus habitat around the Community Forest area in Suka Makmur Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra. The method used is field observation and then making a 200 meter transect at the three observation stations, the first station is an oil palm plantation (3°20'33.1''N 98°31^' 34.8''E), a resident's field (3°20'10.9 ''N 98°31^' 00.6''E), and a rubber plantation (3°18'47.9'0'N 98°30^' 58.2''E). In one station, 5 plots were created with a size of 20 x 20 m and the distance between the plots was 25 m. Data analysis using the Shannon-Wiener index. The results are classified in the high category, namely H′ = 3.634. Where at station one, namely oil palm plantations, 27 types of macroscopic fungi were found with a diversity index H'= 2,639 (medium), at the second observation station, namely people's fields, 24 species were found with a diversity index H'= 2,804 (medium) and at station three gardens In rubber, 29 types of macroscopic fungal species were found with a diversity index H′= 3.194 (high). The types of macroscopic fungi found are from two divisions, namely ascomycota and basidiomycota, 7 classes, 11 orders, 28 families and 59 species. Environmental physical factors such as temperature 24 - 26 °C, pH 5.5 - 7.0, and light intensity 290 - 500 candela.